Milder forms of muscular dystrophy associated with POMGNT2 mutations. (December 2015) - Endo, Yukari; Dong, Mingrui; Noguchi, Satoru; Ogawa, Megumu; Hayashi, Yukiko K.; Kuru, Satoshi; Sugiyama, Kenji; Nagai, Shigehiro; Ozasa, Shiro; Nonaka, Ikuya; Nishino, Ichizo
Abstract : Objective: To determine the genetic variants in patients with dystroglycanopathy (DGP) and assess the pathogenicity of these variants. Methods: A total of 20 patients with DGP were identified by immunohistochemistry or Western blot analysis. Whole-exome sequencing (WES) was performed using patient samples. The pathogenicity of the variants identified was evaluated on the basis of the phenotypic recovery in a knockout (KO) haploid human cell line by transfection with mutated POMGNT2 cDNA and on the basis of the in vitro enzymatic activity of mutated proteins. Results: WES identified homozygous and compound heterozygous missense variants in POMGNT2 in 3 patients with the milder limb-girdle muscular dystrophy (LGMD) and intellectual disability without brain malformation. The 2 identified variants were located in the putative glycosyltransferase domain of POMGNT2, which affected its enzymatic activity. Mutated POMGNT2 cDNAs failed to rescue the phenotype of POMGNT2 -KO cells. Conclusions: Novel variants in POMGNT2 are associated with milder forms of LGMD. The findings of this study expand the clinical and pathologic spectrum of DGP associated with POMGNT2 variants from the severest Walker-Warburg syndrome to the mildest LGMD phenotypes. The simple method to verify pathogenesis of variants may allow researchers to evaluate any variants present in all of the known causative genes and the variants in novel candidate genes to detect DGPs, particularly without using patients' specimens.